2014
DOI: 10.1016/j.jamcollsurg.2013.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Total Pancreatectomy and Islet Auto Transplantation for Hereditary/Genetic Pancreatitis

Abstract: Background Chronic-pancreatitis is a debilitating-disease resulting from many etiologies. The-subset with hereditary/genetic defects (HGP) not only has chronic-pain, but also an increased-risk for pancreatic-cancer. The long-term-outcomes of TP-IAT for chronic pancreatitis due-to-HGP are not clear. Study Design Review of a prospectively-maintained-database of 484 TP-IAT-from-1977-2012 at a single-center. The-outcomes (pain-relief, narcotic-use, β cell-function, health-related quality of-life-measures of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 30 publications
1
90
0
Order By: Relevance
“…Thus, limitations in diagnostic testing and difficulty in distinguishing pancreatitis from other sources of pain complicate the selection of candidates. In addition, there are emerging limited data suggesting that pain responses might be better in those CP patients with genetic mutations (13) compared to those who are alcoholics (14). The risks of insufficient islet mass and central sensitization of pain along with the likelihood of progression of disease should be considered in the timing of intervention.…”
Section: Patient Selection Indications and Timing Of Tpiatmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, limitations in diagnostic testing and difficulty in distinguishing pancreatitis from other sources of pain complicate the selection of candidates. In addition, there are emerging limited data suggesting that pain responses might be better in those CP patients with genetic mutations (13) compared to those who are alcoholics (14). The risks of insufficient islet mass and central sensitization of pain along with the likelihood of progression of disease should be considered in the timing of intervention.…”
Section: Patient Selection Indications and Timing Of Tpiatmentioning
confidence: 99%
“…Dosing of pancreatic enzymes in patients with exocrine insufficiency is highly variable, and many patients are undertreated. Monitoring of nutrition in CP or after TPIAT (fat soluble vitamins, vitamin B12, weight, muscle mass, and bone health) is performed sporadically, depending on the individual center (13, 63). …”
Section: Improving Outcomes After Total Pancreatectomymentioning
confidence: 99%
“…These results confirmed the fact that TP-IAT is effective in preserving b-cell function in patients with CP due to hereditary cases. However, the authors suggested that TP-IAT should be considered earlier in the course of disease, before pancreatic inflammation results in a higher degree of pancreatic fibrosis and deterioration of islet cells function [62].…”
Section: • • Metabolic Outcomes Of Pancreatic Resection Followed By Iatmentioning
confidence: 99%
“…As with other forms of pancreatitis, endoscopic or surgical interventions may also be indicated to alleviate pain. There is growing use of total pancreatectomy with islet autotransplantation (TP-IAT) in the United States, and this appears to be an effective (and radical) treatment in some patients (8,14) (see below).…”
Section: Painmentioning
confidence: 99%
“…Total pancreatectomy with islet autotransplantation may be considered in younger patients for unmanageable pain (13,14). Older patients with longstanding CP may benefit from total pancreatectomy without islet autotransplantation for pain alleviation and to reduce the risk of pancreatic cancer (13,71).…”
Section: Total Pancreatectomymentioning
confidence: 99%